Administration of Glucose at Litter Equalization as a Strategy to Increase Energy in Intrauterine Growth Restricted Piglets - Joanna Klaaborg; Charlotte Amdi (Animals, 2020)
Hyper-prolific sows give birth to large litters and up to 25% of piglets born have been subjected to intrauterine growth restriction (IUGR). The aim of this study was to test whether an oral administration of glucose impacts the survival rate and body weight gain of IUGR piglets at weaning. Different methods (injection versus oral administration of glucose 6 mL or 12 mL, respectively) were tested on IUGR piglets at litter equalization (i.e., when piglets are handled the first time at 5–20 h after birth). Injecting glucose generated the highest whole-blood glucose level + 3 h after treatment, however, after this no differences were observed. Of the 237 IUGR piglets studied, 98 piglets died or were removed from the nurse sow (41%). Rectal temperature at litter equalization (0 h) was related to the survival of the piglets with an average temperature of 37.1 ± 0.1 °C in surviving piglets and 36.6 ± 0.1 °C in piglets that died. In conclusion, providing these extra management actions at litter equalization is too late to help piglets that have a low rectal temperature and are low on energy. More research investigating different management methods to deal with IUGR piglets are needed as many of these underdeveloped piglets will not survive.